Celan and the "Stumbling Block" of Mysticism - Joachim Schulze (Studies in 20th & 21st Century Literature, 1983)
In certain poems, Celan uses concepts that derive in part indirectly, in part directly from mystical sources (Gershom Scholem, Meister Eckhart). In other poems, the reader also finds themes related to mysticism. This discovery raises the question of whether one may read these poems as mystical expressions, or whether they should not in fact be viewed instead as "poetic transpositions" of concepts drawn from the "raw material" of mysticism. Using a specific example, this essay will demonstrate the possibility of reading a poem in a mystical context, i.e. as a mystical expression, and then address the question from two perspectives. First, on the basis of one study that deals with the matter it will demonstrate the difficulties with which any claim for "poetic transposition" must struggle in light of certain aesthetic assumptions and currently accepted definitions of "the poetic." Second, it will focus on the question of whether "aesthetic distance" in Celan's poetry can be established at all. To clarify this concept, it will use Mallarmé's aesthetic reaction to his experience of "nothingness." The essay concludes with a brief reference to the tradition of the "mystical aphorism" as a genre or type to which one might assign the corresponding poems by Celan.
Keywords: Paul Celan; mystic; Gershom Scholem; Meister Eckhart; mysticism; poetic transpositions; poetry; poem; mystical expression; aesthetic distance; Mallarmé; aesthetic; nothingness; mystical; aphorism